What approach should we take for the incidental finding of increased 18F-FDG uptake foci in the colon on PET/CT? - Simsek, Fikri S.; Ispiroglu, Murat; Tasdemir, Bekir; Koroglu, Reyhan; Unal, Kemal; Ozercan, Ibrahim H.; Karabulut, Koray (Lippincott Williams & Wilkins, 2015)
Introduction F-18-Fluorodeoxyglucose (F-18-FDG) PET/CT represents an imaging modality that is gaining increasingly more prominence in screening, staging, and therapeutic monitoring of malignant diseases. An incidental focus of uptake in different regions of the body is not an uncommon finding during PET/CT imaging. Patients with incidental gastrointestinal tract findings comprise approximate to 3% of the overall patient group. The aim of the current study was to provide contributory information in relation to the answer on the most appropriate approach in cases with incidental colonic F-18-FDG uptake. Patients and methods A retrospective examination was performed on PET/CT results of 5258 patients. Of these, 152 were recommended to undergo colonoscopy because of the presence of suspicious foci and 31 underwent colonoscopy within 60 days with biopsy from all visible lesions. These dates were also examined. Results Of the 24 patients undergoing colonoscopy with a suspicion of malignancy, five (20.83%) had no pathological findings. Of the 19 (79.17%) cases with a pathological finding in endoscopy, histopathology showed a benign lesion in five (20.83%), premalignant lesion in seven (29.17%), and a malignant lesion in seven (29.17%). Among seven patients undergoing colonoscopy because of a suspicion of inflammatory bowel disease, five were free of pathological signs and two patients with pathological endoscopy findings had nonspecific inflammation as documented by histopathological examination. Conclusion Colonoscopic and histopathological examination of the increased foci of colonic F-18-FDG uptake incidentally detected at PET/CT seems to be a plausible approach. Copyright (C) 2015 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: colonic F-18-FDG uptake; incidental; PET/CT